The effect of job training and work environment on employee performance at PT. Suri Motor Indonesia - Herman Susilo; Mega Indah Edityawati; Suhardi Suhardi (International Journal of Applied Finance and Business Studies, 2026)
Study this aim for know influence training work and environment Work to performance employees at PT. Suri Motor Indonesia. The research method used is approach quantitative with technique analysis multiple linear regression. Hypothesis testing done through a number of stages, namely the F test, t test, coefficient determination (R²), as well as identification the most dominant variable. The results of the analysis show that equality regression obtained is: Y = 1.378 + 0.280X₁ + 0.605X₂. Based on the F test, it is obtained mark F count of 62,527 > Ftable 3,080 with mark significance of 0.000, which means training work and environment Work in a way simultaneous influential significant to performance employees. Furthermore, the value coefficient Adjusted R² determination of 0.524 shows that 52.4% of the variation performance employee can explained by both variables independent, whereas the remaining 47.6% is explained by other factors outside the research model. Based on the t-test, training Work influential significant in a way partial to performance employees (t hitung = 3.975 > ttabel = 1.98209; sig. = 0.000), as well as the environment work (thitung = 7.521 > ttabel = 1.98209; sig. = 0.000). From the results of the standardized beta coefficients, it is known that that environment Work is the most dominant variable influence performance employee with beta value of 0.550. With thus, it can concluded that improvement training work and creation environment good work plays a big role in increase performance employee.